Place assimilation across words in running speech: Corpus analysis and perception - Zimmerer, F; Reetz, H; Lahiri, A (Acoustical Society of America, 2009)
Place assimilation can lead to neutralization of segmental contrasts. It is controversial, however, to what extent such neutralizations actually happen in natural speech. This study examines: (i) the degree to which regressive place assimilations occur in word final consonants in conversational German, and (ii) whether these assimilations are perceived as neutralized by listeners. The production analysis, based on spontaneous speech, shows that complete assimilations do take place in conversational speech and that there is a clear asymmetry between coronal versus labial and dorsal segments. Furthermore, function words show a higher degree of assimilation than lexical words. Two experiments examined the effects of assimilation on perception. A forced choice reaction time perception experiment, using nasal stimuli from the corpus, examined how fast and accurately listeners identified sounds in different segmental contexts. Results indicate that (a) with equal accuracy and speed, listeners identified original and assimilated [m]s; (b) unassimilated-/m/s were identified equally well across contexts, but not unassimilated/n/s. A free transcription experiment reproduced these findings. An acoustic analysis provides further evidence that regressive place assimilation across word boundaries can result in absolute neutralization of place contrasts in running speech. The results support models predicting asymmetries between coronal versus labial and dorsal consonants.